Keanekaragaman KEANEKARAGAMAN SPESIES BURUNG DIURNAL DI CAGAR ALAM NUSAKAMBANGAN TIMUR - Iftah Sadjad Ahmadi; Suhestri Suryaningsih; Erie Kolya Nasution (BioEksakta : Jurnal Ilmiah Biologi Unsoed, 2022)
Birds are members of a group of vertebrate animals belonging to the aves class. Birds play an important role in ecosystem components to support an organism's life cycle. The high diversity of bird species is supported by the high diversity of habitats that function as places for finding food, drinking, resting and breeding. Nusakambangan is an island with an area of ​​240 km2 with lowland natural forest, coastal forest and mangrove forest. Research in 2003 and 2004 western part of Nusakambangan has 93 bird species and in 2006, bird species in the type of habitat for sandy coastal forest, pamah forest, limestone forest, grasslands, young shrubs, and old shrubs contained 121 species of birds. This study aims to determine the diversity of bird species in the Nusakambangan Timur Nature Reserve. This research was conducted using a survey method with a point count technique. The data were analyzed by simple descriptive and then displayed in tabular form. There are 46 bird species from 25 families with a diversity index of 2.5456 and a dominance index of 0.1027.